Si morbus aevitasve vitium escit - Zabłocki, Jan (Prawo Kanoniczne, 1994)
Considering the Twelve Tables today, it seems important to question whether the statute was humanitarian. It became also problematic for Roman lawyers six centuries after its passage. Aulus Gellius in Noctes Atticae (Gell.20.1.1)55) presents the dispute between philosopher Favorinus from Areate and Sextus Caecilius, who was a jurist. One of the main discussed provision was: Si morbus aevitasve vitium escit, [qui in ius vocabit] iumentum dato. Si nolet, arceram ne sternito (tab. 1.2 Gell.20.1.25). The philosopher alleged it was inhuman to interdict the delivery of a comfortable vehicle for a seriously diseased or for an old man who was unable to walk as well as to command the transport in ius on beasts of burden (Gell.20.1.11). Arguing that verbis moribusque sententia legum conprehensa est, the lawyer claimed that the Twelve Tables were humanitarian (Gell.20.1.24). It is because the provision had a different meaning (Gell.20.1.26), as morbus meant not a serious illness, which was called morbus sonticus by Decemviri, but usual problems with walking (Gell.20.1.27). Similarly, the iumentum was not only a beast of burden, but a country waggon as well (Gell.20.1.28). The country waggon should be delivered by a plaintiff to ill or aged dependents. However, if defendants had not been satisfied with the ordinary waggon, the plaintiff did not need to offer the comfortable vehicle (Gell.20.1.29)30). The jurist’s argumentation convinced the philosopher and was accepted by their audience.